Performance evaluation of microstrip patch antenna with different DGS shapes and substrate materials - Singh, Jashan Preet (My University, 2015)
In today’s era, wireless communication system is the fastest growing segment in the communication research field. Rapid growth in the wireless technologies in the last decade have made antenna designing more challengeable. In present scenario, technology demands antenna which can operate on different wireless frequency bands and should have features like low cost, minimal weight, low profile that are capable of maintaining high performance over large frequency spectrum. Therefore microstrip patch antenna (MPA) with defected ground structure is the good candidate for these type of multiband applications having stable performance even at higher frequencies and provides large bandwidth. DGS is analysed in terms of its superior properties, which enables the designers to easily realize the various microwave applications which are impossible with standard techniques. Wireless local area network (WLAN) and Worldwide Interoperability for Microwave Access (WiMAX) have been widely used in mobile devices such as handheld computers and smart phones. These two techniques have been widely considered as a reliable, cost-effective, and high-speed data connectivity solution, also provides user mobility. This research work focuses on the designing, simulation and fabrication of microstrip patch antenna with defected ground structure for WiMAX/WLAN tri-band applications. The main advantage of multiband antenna has been achieved by varying the substrate material along with shapes of patch and ground defects. The major improvements had been achieved in gain, efficiency and return loss because of above mentioned variations in traditional MPA’s. The proposed antennas have compact size with planer structure consisting of patch, microstrip feed line and a defected ground plane. The traditional antennas have been analysed and fabricated on the FR4 substrate but the antenna proposed in this thesis work has been fabricated on the ROGER RO3003 substrate due to various advantages. The analysis and designing have been optimized with the aid of CST Microwave Studio® version 2014. Further, simulation results of CST Microwave Studio® have been supported by the experimental results of fabricated proposed antennas. In this research work two novel antenna designs have been proposed for tri-band applications. The first design have square shape metal strip patch enclosing a U-shape metal strip having curved shape ground plane with three square shape ground defects of different dimensions. The peak return losses obtained of this antenna in three frequency bands are -19.33 dB at 2.4 GHz, -24.25 dB at 3.5 GHz and -39.5 dB at 5.45 GHz. The bandwidth obtained is 0.33 GHz (2.20-2.53 GHz), 1.15 GHz (3.09-4.24 GHz) and 0.86 GHz (5.03-5.89 GHz) respectively. The peak gains obtained in three operating frequency bands are 2.81 dBi, 2.65 dBi and 4.38 dBi respectively. The second design antenna have Y-shaped metal strip enclosed by a circular shape metal strip and curved shape ground with three polygon defects of different shape and dimensions. The peak return losses obtained of this antenna are -20.41 dB at 2.45 GHz, -26.42 dB at 3.34GHz and -31.97 dB at 5.5GHz respectively. The bandwidth of three bands are 0.3GHz (2.27-2.57GHz), 1.17GHz (3.07-4.24GHz) and 1.302GHz (4.837-6.139GHz). The isotropic peak gains of three bands are 2.66 dBi, 2.58dBi and 4.5 dBi respectively.
ME-Wireless Communication-Thesis
Keywords: MPA; DGS; CST; ROGER RO3003; electronics; ece; wiereless communication